2019
DOI: 10.17227/rce.num77-9571
|View full text |Cite
|
Sign up to set email alerts
|

Creencias distorsionadas sobre la violencia de género en docentes en formación de Colombia

Abstract: La violencia contra las mujeres es un problema social y de salud pública que tiene lugar en todos los países. El presente artículo de investigación analiza las creencias distorsionadas sobre los roles de género y la violencia contra las mujeres en la pareja en una muestra de docentes en formación. La muestra está conformada por 443 estudiantes (71,6 % mujeres y 28,4 % hombres) de distintas universidades colombianas. Los resultados reportan diferencias estadísticas entre hombres y mujeres en la aceptación de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
0
13
0
9
Order By: Relevance
“…The education system is one of principal spaces for socialisation and as such, plays a central role in achieving a just and egalitarian society (Azorín, 2017;Fabes et al, 2018;Pinedo et al, 2018;Sáez-Rosenkranz et al, 2019). Schools and teachers should thus be major forces for social change rather than passive spectators (Bonilla-Algovia & Rivas-Rivero, 2019;Carretero & Nolasco, 2019;Cordón et al, 2019;Gray & Leith, 2004;Gullberg et al, 2018;Mai & Brundrett, 2019;Rebollo et al, 2011b;Sáenz del Castillo et al, 2019). It is therefore necessary to pay attention to those elements, such as sexist ideology, that can form part of the hidden curriculum (Maceira, 2005) and legitimise structural gender inequality (Brandt, 2011;Glick et al, 2000;Taşdemir & Sakallı-Uğurlu, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The education system is one of principal spaces for socialisation and as such, plays a central role in achieving a just and egalitarian society (Azorín, 2017;Fabes et al, 2018;Pinedo et al, 2018;Sáez-Rosenkranz et al, 2019). Schools and teachers should thus be major forces for social change rather than passive spectators (Bonilla-Algovia & Rivas-Rivero, 2019;Carretero & Nolasco, 2019;Cordón et al, 2019;Gray & Leith, 2004;Gullberg et al, 2018;Mai & Brundrett, 2019;Rebollo et al, 2011b;Sáenz del Castillo et al, 2019). It is therefore necessary to pay attention to those elements, such as sexist ideology, that can form part of the hidden curriculum (Maceira, 2005) and legitimise structural gender inequality (Brandt, 2011;Glick et al, 2000;Taşdemir & Sakallı-Uğurlu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus in the literature that the education system, as a space for socialisation, and teachers, as the agents of socialisation, play a major role in mitigating sexism, gender stereotypes and inequality between men and women (Azorín, 2017;Bonilla-Algovia & Rivas-Rivero, 2018;Fabes et al, 2018;Pinedo et al, 2018;Sáez-Rosenkranz et al, 2019); however, as research in different countries has shown, education institutions are not exempt from gender bias or obstacles that impede the attainment of equality (Biemmi, 2015;Brundrett & Dung, 2018;Gray & Leith, 2004;Mai & Brundrett, 2019;Sáenz del Castillo et al, 2019;Sánchez, 2002). The sexist attitudes of education agents can be one of the main barriers for the development of a feminist and egalitarian school (Bonilla-Algovia & Rivas-Rivero, 2019;Carretero & Nolasco, 2019;Cordón et al, 2019). Throughout their lives, teachers adopt some beliefs that may interfere with their behaviour in the classroom and with their relationship with students (Sales-Oliveira et al, 2016), so that stereotypical gender beliefs can influence teachers' perceptions, discourses and educational practices (Matheis et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Si los y las futuras responsables de educar a las nuevas generaciones han asumido estas creencias irracionales, es necesario intervenir en la deconstrucción de tales valores haciendo que las acciones emprendidas por conseguir la igualdad sean una realidad y no una declaración de intenciones. Además, las estadísticas sobre violencia de género en España hacen que la intervención y la educación sean una prioridad (Bonilla y Rivas, 2018; Bonilla-Algovia y Rivas-Rivero, 2018; Bonilla-Algovia y Rivas-Rivero, 2019;Carbajosa y Boira, 2013).…”
Section: Discussionunclassified
“…Por ello, las instituciones educativas tienen un papel muy relevante en la deconstrucción del amor romántico y en el desarrollo de una socialización basada en la igualdad de género. En este sentido, el profesorado es clave y sobre este recae la responsabilidad de modificar los modelos tradicionales basados en la desigualdad entre mujeres y hombres (Bonilla-Algovia y Rivas-Rivero, 2019).…”
unclassified